Mild cognitive impairment in idiopathic parkinson's disease without dementia. (2017)
Mild Cognitive Impairment (MCI) is a non-motor common symptom of idiopathic Parkinson's disease (PD) without dementia. Different studies have shown that the MCI is a strong predictor for dementia in advanced clinical stages. Early and timely identification of the MCI in PD allows to generate new lines of treatment, specifically, Neurorehabilitation, functional techniques, tended to improve the quality of life for people diagnosed with PD. It was found that individuals had deficits to retain stimuli in a time given (sustained attention), inability to consolidate information and new learning, as well as alterations in executive functions and visuospatial functioning. New lines of research should not only focus on defining MCI. Non-pharmacological treatment options are a scientific trend that will slow down the disease and improve emotional, individual, and family aspects of people with PD as far as possible. © 2017, Scientific Publishers of India. All rights reserved.